A dream in the world : poetics of soul in two women, modern and medieval - Van Löben Sels, Robin E., 1938- (Brunner-Routledge, 2003)
How can science and religion co-exist in the modern discipline of psychotherapy? A Dream in the World explores the interfaces between religious experience and dream analysis.